Medical Transport for 769 COVID-19 Patients on a Cruise Ship by Japan Disaster Medical Assistance Team. (5th December 2020) - Anan, Hideaki; Kondo, Hisayoshi; Takeuchi, Ichiro; Nakamori, Tomoki; Ikeda, Yu; Akasaka, Osamu; Koido, Yuichi
ABSTRACT: The Diamond Princess cruise ship, carrying 3711 passengers and crew members, docked at Yokohama Port in Japan on February 3, 2020. A quarantine was immediately instituted because 1 passenger who had disembarked in Hong Kong was confirmed to have tested positive for coronavirus disease 2019 (COVID-19). After the quarantine began, all passengers and crew were tested using the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) polymerase chain reaction assay on the ship, 696 of whom tested positive. In total, 769 patients, including 696 with COVID-19, required transport to a hospital. The Japan Disaster Medical Assistance Team (DMAT) successfully picked up and safely transported the COVID-19 patients using a novel classification system to prioritize patients. The Japan DMAT transported 203 patients to hospitals in Kanagawa and another 566 patients to hospitals in 15 different prefectures.